KAJIAN SOSIAL-EKONOMI DALAM PELAKSANAAN SISTEM INTEGRASI SAPI-KELAPA SAWIT (SISS) DI PT AGRICINAL KAB. BENGKULU UTARA - Purwoko, Agus; Sumantri, Bambang (Jurnal AGRISEP, 2008)
The research  was conducted to study factors that correlated with harvest labours’ motivation to join the program of systematic cow cattle integration in oil palm plantation (SISS), to investigate the harvest labours’ net income from SISS and its contribution to family income, and  to examine factors that were influencing the return rate of credit. The research was conducted in PT Agricinal, an oil palm plantation in North Bengkulu Regency.  The respondents for the research consisted of 83 harvest labours were selected from 3 afdellings proporsionally using simple random sampling method.  Data were analyzed using Spearman’s Rank-Order correlation coefficient and multiple linear regressions.  Harvest labours’ age, net income from SISS, the number of dependency family, empathi, and dogmatism were significantly correlated with the labours’ motivation to join the program of SISS.  The average of harvest labours’ monthly net income from SISS was Rp. 1.23 million and its contribution to family income was 98.71 percents.  While the return rate of credit was only 43.27 percent and it was significantly influenced by the harvest labours’ education and the total of credit.    PT Agricinal should be maintaining the harmony relationship with harverst labours in order to improve their work motivation.  In addition, the regulation of SISS program should be conveyed not only in oral but also in writing in order to guarantee the harvest labours to do their job.